(untitled) - Pickett, William P. (New York, 2005)
Leaders of the Americas is an intermediate and high-intermediate two-book supplementary reading and vocabulary series. Students learn about historical figures of North and South America while improving their core reading skills, building vocabulary, and practicing test taking.
Keywords: Readers,English language,Tiếng Anh thực hành; Biography,Textbooks for foreign speakers,Sách giáo khoa dành cho người nước ngoài